Cassava root and leaf flour in poultry feed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
In the Brazilian state of Amazonas, the poultry-farming industry is experiencing a number of difficulties due to high production costs brought about by the expense and scarcity of the raw materials used to make feed for domestic fowl. The main...